A integração de conteúdo jornalístico à publicidade: trocas simbólicas entre as marcas Petrobras e Superinteressante - Gomes Neto, Rogério (2009)
This article examines the institutional advertisements discourse of the Brazilian state-owned company Petrobras. The analyzed pieces comprehend ads published between the years of 2006 and 2007 in the Superinteressante magazine, issued by editora Abril. The objective is to identify the news configurations of the information and how to occur the symbols exchange in the appropriation of editorial content with advertising. To do so, it was used the Discourse Analysis methodology.(AU)